The Economics of Eisenhower: A Symposium - Harris, S. E.; Slichter, S. H.; Samuelson, P. A.; Fellner, W.; Shaw, E. S.; Groves, H. M.; Wallich, H. C.; Harberger, A. C.; Goldfinger, N. (The Review of Economics and Statistics, 1956)
S. E. Harris, S. H. Slichter, P. A. Samuelson, W. Fellner, E. S. Shaw, H. M. Groves, H. C. Wallich, A. C. Harberger, N. Goldfinger, The Economics of Eisenhower: A Symposium, The Review of Economics and Statistics, Vol. 38, No. 4 (Nov., 1956), pp. 357-385